A context-dependent induction of natal habitat preference in a generalist herbivorous insect. (22nd December 2017) - Lhomme, Patrick; Carrasco, David; Larsson, Mattias; Hansson, Bill; Anderson, Peter
Abstract : Some herbivorous insects remember their childhood, but they recall only the nice memories! We show in a moth that host-plant odor exposure associated with high-quality food during larval stage induces a preference shift in adults for the experienced plant, whereas no such preference shift was found for odors associated with low-quality food. Abstract: In many species, adults exploit sensory information experienced in their natal habitat when searching for resources. This behavioral plasticity may help animals to establish themselves in new habitats by quickly locating suitable resources and avoiding unsuitable resources in complex environments. However, the processes guiding positive or negative natal habitat preference induction (NHPI) remain poorly understood. In the polyphagous moth Spodoptera littoralis, earlier studies have shown that female innate host-plant preference is modulated by larval feeding experience. In this context, the aim of this study was to investigate how variability in food quality associated with habitat olfactory cues can modulate NHPI in this species. We found that larvae showed appetitive or aversive responses to the experienced plant olfactory cues based on their values as predictors of food quality. Furthermore, larval exposure to host-plant olfactory cues alone induced oviposition preference for these plants in adult females, but only when the females had been feeding on high-quality food as larvae. Females reared on poor quality food retained their innate plant oviposition preference as adults. These results show that NHPI in S. littoralis is context-dependent and based on food quality with which olfactory cues are associated. They also suggest that larval experience to plant olfactory cues alone is sufficient to modulate the adult host-plant preference. Finally, this study suggests that polyphagous insects with particular innate plant preferences may only show phenotypic plasticity in this trait when the fitness benefits are high.